Synthesis of the cardioid crank slider mechanism with double working strokes - HOU Yujie; HAN Jiguang (Jixie chuandong)
ObjectiveIn order to obtain a slider mechanism with double working strokes and meet the double feeds demand of some automatic machine tools, a cardioid crank slider mechanism with double working strokes was obtained by using a planetary mechanism which can generate double rings motion curve to drive the slider Ⅱ group.MethodsThe mechanism analysis was carried out. The calculation methods of the parameters such as limit position, working stroke, crank existence condition, minimum length of the connecting rod and minimum transmission angle were given. The influence of the mechanism parameters on the working stroke and minimum transmission angle were studied. Based on the monotone characteristic between the mechanism parameters and the working strokes, a simple iterative method was proposed for the mechanism synthesis according to double working strokes.ResultsThe proposed mechanism provides a basis for the design of the mechanism with double working strokes.